The executive guide to enterprise risk management - Chappell, Christopher; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
An executive level guide to implementing or extending an enterprise risk management (ERM) framework in an organization. Avoiding complex modeling topics, and unnecessary theory, this book cuts to the heart of the topic, describing what ERM is, why it is important, what constitutes ERM and how it can be implemented to add value to an organization.
Keywords: Science